Modelling Intention to Use ERP Systems among Higher Education Institutions in Egypt: UTAUT Perspective - Mohamed Soliman, Mohamed Soliman; Karia, Noorliza; Moeinzadeh, Soroush (International Journal of Supply Chain Management, 2019)
Firms strive to achieve the sustainable competitive advantage in diverse and changing marketplaces. Coping with such circumstances has required firms to align information technology with business strategy in order to exploit their capabilities and change business practices. In this regard, an Enterprise Resource Planning (ERP) system has become increasingly important for organizations to build strong capabilities, improve operational performance, enhance business decision making and compete in a global business context. In other words, an ERP system integrates an organizations resources and also involves business processes and organizational changes. With the ubiquitous growth of IS investment, implementation of ERP systems has grown strongly. Recently, Higher Education Institutions (HEIs) have started to adopt ERP systems. An example is Egypt, where they have done so to increase their competitiveness in the global market. However, historically, ERP implementation has been shown to have a high failure rate, which is one of the main reasons users resist using the ERP system. Conversely, users acceptance of the ERP system is the key to the ERP implementation. Thus, this study attempts to find out the important factors that affect end users intention to use the ERP system during the pre-implementation phase of the ERP lifecycle in the higher education context. The Unified Theory of Acceptance and Use of Technology (UTAUT) with minor adjustments is the basis of this study. Ultimately, the findings of this research could enrich employees' experience by giving HEIs a tool for better understanding those factors affecting their ability to effectively utilize ERP systems. The proposed model has the ability to enhance the current level of the motivating factors influencing employees motivation to utilize ERP systems.